High Potential Promotion within the Framework of Diversity Care - Navarro Guillén, María Isabel (2022)
In Costa Rica important advances have been made in the promotion and care of the students with high potential. Despite the legislation progress, it exists a difficulty in reaching conceptual consensus keeping different definitions and uses of the following terms: high potential, high endowment, and talent. Additionally, the roots of the normality approach that insist on privileging a student’s group with identification processes and procedures for perfecting their potentialities and talents are supported. Based on this reality, the author finds necessary to consider on the possibility of redirect the existing actions in a way that guarantee education quality for the entire student´s community. This creates important challenges since it requires conceiving diversity as an inherent characteristic of human beings. And, as part of the attention to this heterogeneity, it must be guaranteed that each student has the opportunity to take part in psycho-pedagogical evaluation processes and receive prompt and individualized mediation with trained professionals on the implementation of a flexible curriculum that allows everyone to perfect and express their potentialities.